Analisis Isi Kampanye Politik Anies Rasyid Baswedan Pada Pemilihan Presiden 2024 di Instagram - Pratama, Andi Agustian; Saputera, Hery; Ali, Gustrianti M.; Wijanarko, Totok Ony; Hutapea, Edison Bonartua (FISIP Universitas Bung Karno, 2024)
Abstract Social media plays an important role in relation to political campaigns carried out by 2024 presidential candidates because some politicians use social media to interact with sympathizers and supporters. Anies Baswedan makes good use of the Instagram site to convey political messages through the media so that it is easy to build chemistry. This research aims to determine Anies Baswedan’s political campaign on Instagram by using content analysis, namely looking at (1) Anies Baswedan’s personality on Instagram (2) Anies Baswedan’s political key massage displayed on Instagram. This research uses a qualitative approach. The informants for this research were 145 uploads which constituted the total on Instagram @AniesBaswedan in January 2024. The instruments used in content analysis research are presented in the form of analyzing political campaigns consisting of campaign strategies, public interactions and visual symbols and messages the research results show that. The result of the research show that Anies Baswedan consistently conveys his campaign messages via media social and Desak Anies campaign is effective in influencing the face of modern democracy. Keywords: Campaign, Anies Baswedan, Instagram, Content, Presidential elections